PTSD and the War of Words. (April 2018) - Chekroud, Adam M.; Loho, Hieronimus; Paulus, Martin; Krystal, John H.
Trauma-related symptoms among veterans of military engagement have been documented at least since the time of the ancient Greeks. 1 Since the third edition of the Diagnostic and Statistical Manual in 1980, this condition has been known as posttraumatic stress disorder, but the name has changed repeatedly over the past century, including shell shock, war neurosis, and soldier's heart. Using over 14 million articles in the digital archives of the New York Times, Associated Press, and Reuters, we quantify historical changes in trauma-related terminology over the past century. These data suggest that posttraumatic stress disorder has historically peaked in public awareness after the end of US military engagements, but denoted by a different name each time—a phenomenon that could impede clinical and scientific progress.